DEPUTIES’ LIABILITY FOR ADMINISTRATIVE OFFENCES - Гончарук, Степан Тихонович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: to investigate the issue of people’s deputies and deputies of local councils liability for their administrative offences and represent separate suggestions for making appropriate changes to the current administrative-delict legislation of Ukraine. Methods: the research has been carried out using generally accepted methods of scientific knowledge, including semantic-cognitive, analytical, comparative-legal, statistical, etc. Results: the particularities of deputies’ legal liability for the commission of administrative offences have been highlighted, the suggestions for the improvement of the current administrative-delict legislation of Ukraine, in particular to change the relevant article of the Code of Ukraine on Administrative Offences have been determined. Discussion: deputies’ liability for administrative offences issues. The article is devoted to the research of administrative liability of people’s deputies and deputies of local councils for their administrative offences, analysis of material aspects of this liability, the legal characterization of certain administrative offences, as well as processual peculiarities of the above mentioned subjects liability for their administrative offences. Today, the current legislation of Ukraine does not have regulatory provisions regarding the peculiarities of administrative liability of people’s deputies. However, the Constitution of Ukraine, certain laws foresee the specific of these persons’ legal status, in particular regarding their immunity and the possibility of legal liability on a general basis. The article analyzes the legal nature of certain categories of administrative offences for which, in the author’s opinion, people’s deputies must be responsible and have the administrative liability on the general basis, types of administrative penalties that cannot be applied to deputies. The issues of the substantive, subjective and territorial jurisdiction of cases on such offences have been investigated. Certain suggestions regarding the appropriate changes to the current administrative-delict legislation of Ukraine have been given. According to the author’s opinion, for the commission of administrative offences, people’s deputies should be liable in a special order. In particular, for the commission of the majority of administrative offences, it is better to apply disciplinary liability in accordance with the Regulations of the Verkhovna Rada of Ukraine. For the commission of certain administrative offences, they should be subject to administrative liability on a general basis. These are offences related to corruption, violation of electoral legislation, non-fulfilment of legal requirements of the National Anti-Corruption Bureau of Ukraine and the National Agency for Prevention of Corruption officials, with certain violation of the traffic rules, etc. At the same time, such penalties cannot be applied to them as a deprivation of the right to occupy certain positions or perform a certain activity, public works, socially useful works, correctional works, administrative arrest, arrest with keeping on the guardhouse. The peculiarities of their liability should be regulated and detailed in the Code of Ukraine on Administrative Offences, first of all, by supplementing it with Article 15-1 «Liability of people’s deputies and deputies of local councils».